“UMKM Go Export” training for KSBI Community in South Jakarta - Sofilda, Eleonora; Hamzah, Muhammad Zilal; Nurhaida, Dida; Islami, Wardah; Munawar, Muhammad Agil (Community Empowerment, 2025)
The “UMKM Go Export” program is a community engagement initiative aimed at improving the export readiness of Micro, Small, and Medium Enterprises (MSMEs) under the Komunitas Sukses Berjamaah Indonesia (KSBI). The one-day training was conducted using a participatory approach and adopted the “9 Steps to Enter Export Markets” curriculum, covering topics from business readiness, product standards, market mapping, international trade regulations, digital marketing, to export transactions and networking. Pre-test and post-test results showed a significant increase in knowledge, from 58.2 to 83.6. Around 80% of participants were able to draft a basic export plan, and 70% successfully created digital business accounts. Despite the short duration, participants' engagement in simulations, group discussions, and follow-up mentoring reinforced their readiness to compete globally. This program serves as a replicable model for empowering MSMEs in sustainable export development.